A Meta-Analysis of the Influence of Instructional Media on Speaking Learning - Lispridona Diner; Zukhaira Zukhaira; Sherly F. Lensun (Bina Nusantara University, 2021)
The research analyzed several related studies focusing on instructional media or learning materials and speaking learning that emphasized the development of media for learning activity. Employing a meta-analysis method, the research explored several national journal articles. Meta-analysis was a quantitative study, given its characteristics utilize statistical calculation for a practical purpose, i.e., arranging and extracting information from many data where the process could not be performed using other methods. This meta-analysis research was aimed at identifying the validity level of each data collection. Based on the results, the research concludes that instructional media development for learning speaking activities will be effective if the media are applied in universities. From the perspective of learning materials, the media will be helpful if all of the contents are applied in a book used for the learning process. This is because the teacher’s book summarized everything that a teacher needed for the class, thus allowing successful and directed learning stages and more accurate accomplishment of learning objectives. From the aspect of learning, the speaking skills should focus on the types of conversation, concerning the basic level of speaking proficiency in a foreign language learning is more efficacious than the skills needed in a conversation.